2006
DOI: 10.4161/psb.1.6.3518
|View full text |Cite
|
Sign up to set email alerts
|

Ozone-Induced Cell Death Mediated with Oxidative and Calcium Signaling Pathways in Tobacco Bel-W3 and Bel-B Cell Suspension Cultures

Abstract: Ozone (O 3 )-induced cell death in two suspension-cultured cell lines of tobacco (Nicotiana tabacum L.) derived from Bel-W3 (hyper-sensitive to O 3 ) and Bel-B (highly tolerant to O 3 ) varieties were studied. By exposing the newly prepared cell lines to the pulse of ozonized air, we could reproduce the conditions demonstrating the difference in O 3 sensitivity as observed in their original plants, depending on the exposure time. Since O 3 -induced acute cell death was observed in the dark, the requirement for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 38 publications
4
37
0
Order By: Relevance
“…However, O 3 also induced cell shrinkage, another hallmark of the PCD process in both plant and animal cells [35], [59]. These data fulfill the widely accepted criteria for PCD and confirm that our model responds to acute O 3 exposure in the same way as previously described for other plants [3], [4], [5], [10].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, O 3 also induced cell shrinkage, another hallmark of the PCD process in both plant and animal cells [35], [59]. These data fulfill the widely accepted criteria for PCD and confirm that our model responds to acute O 3 exposure in the same way as previously described for other plants [3], [4], [5], [10].…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, addition of Ca 2+ chelators or Ca 2+ channel blockers resulted in a significant inhibition of an O 3 -induced [Ca 2+ ] cyt increase and subsequent cell death suggesting that the uptake of extracellular Ca 2+ via the activation of PM Ca 2+ channels is required for the induction of active cell death [4], [10]. A change in [Ca 2+ ] cyt was detected in Arabidopis cells expressing aequorin in response to O 3 , as shown in Figure 3A.…”
Section: Resultsmentioning
confidence: 88%
“…Evans blue was added to the cell suspension culture, following 10 min of calcium measurements after Cu application. Cells were further incubated for 1 h in order to fully develope and detect the cell death as described by Kadono et al (2006). After terminating the staining process by washing, stained cells were counted under microscopes.…”
Section: Determination Of Cell Deathmentioning
confidence: 99%
“…Induction of cell death by oxidative stresses accompanying the generation of reactive oxygen species (ROS) is often mediated by early signaling events such as calcium infl ux via ROS-mediated activation of calcium channels on the plasma membrane (Kadono et al, 2006). Our previous studies have revealed that various phytotoxic metals such as Al and 15 rare earth elements induce an acute generation of ROS, such as superoxide anion radicals, by stimulating the plant NADPH oxidase activity (Kawano et al, 2001(Kawano et al, , 2002(Kawano et al, , 2003 and, as a consequence, ROS stimulates the opening of ROS-responsive calcium channels on the surface of plant cells (Kawano et al, 2003(Kawano et al, , 2004.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] One of key signaling events contributing to crosstalk in plant responses to abiotic stress would be transient increase in cytosolic free calcium ion concentration stimulated by generation of ROS through ROS-dependent activation of calcium channels on the vacuolar and/or plasma membranes. 1,4 Impact of various ions of transition metals, chiefly of copper, on oxidative and calcium signal transductions leading to cell death in plant cells have been documented to date. Among such metals, copper is known to be a phytotoxic metal which reportedly induces a series of biological and chemical reactions in plant cells including the burst of reactive oxygen species production and stimulation of calcium channel opening allowing a transient increase in cytosolic calcium concentrations.…”
mentioning
confidence: 99%